Hepatic Encephalopathy in Malaria or Artesunate Toxicity: A Dilemma in Diagnosis - Gopakumar, K. G.; Baliga, Kiran; Keshav, Murali; Baliga, Santharam (Journal of Pediatric Infectious Diseases, 2018)
Malaria remains an overwhelming problem with around 214 million cases reported worldwide each year. It remains a major health problem in the tropical developing countries and India accounts for 70% of the total malaria incidence in the Southeast Asia region. Even though, artesunate, a novel drug used in the treatment of chloroquine-resistant cases of Plasmodium falciparum infection causes transient transaminitis (elevation of alanine and aspartate transaminases), hepatitis and hepatic encephalopathy are very rare. We encountered a child with falciparum malaria, who accidently ingested artesunate tablets (16 mg/kg) and developed hepatic encephalopathy with clinical and biochemical improvement in a matter of 4 to 5 days. There are only a few reports of children with malaria developing hepatic encephalopathy, with or without coinfection with hepatotropic viruses. Also, there are no reports of hepatic encephalopathy secondary to artesunate overdose, creating a dilemma in diagnosis and management.
Keywords: malaria; hepatic encephalopathy; artesunate; children